Carbonation resistance of concrete treated with nano-SiO2- modified polymer coatings - Li, Guo; Cui, Hangyuan; Hu, Weijian; Zhou, Jiacheng (Journal of Asian Concrete Federation, 2019)
This work investigated the effects of nano-SiO2 incorporation on the carbonation resistance of polymer-coated concrete. Three types of organic film-forming coatings, namely, polyurethane, chlo- rinated rubber, and epoxy resin coatings, were modified with 0.4, 1.2, or 2.0 wt.% nano-SiO2 particles. Concrete specimens were then treated with the modified coatings and subjected to accelerated carbona- tion experiments after periodic ultraviolet irradiation. The macro- and microappearances of the coatings after ultraviolet aging were also observed. Results indicated that the carbonation resistance of polymer- coated concrete samples gradually decreased as the polymer coating aged. The incorporation of nano- SiO2 improved the short-term carbonation resistance of coated concrete by increasing coating density and reducing microdefects in the coating film. The presence of nano-SiO2 strengthened the long-term carbonation resistance of coated concrete by shielding and absorbing ultraviolet light and attenuated coating aging. Excessive nano-SiO2 content, however, weakened the carbonation resistance of coated concrete. Thus, a nano-SiO2 dosage of approximately 0.4 wt.% should be applied to develop concrete coatings with the optimal carbonation resistance.